Can audit improve patient care? Effects of studying use of digoxin in general practice. Issue 6641 (9th July 1988) - Anderson, C. M.; Chambers, S.; Clamp, M.; Dunn, I. A.; McGhee, M. F.; Sumner, K. R.; Wood, A. M.
Abstract : A survey of monitoring of digoxin treatment in five practices examined the indications for prescribing digoxin, its long term use, and how its use could be monitored. These data were used to generate a protocol for monitoring treatment with digoxin in general practice. The findings of the survey and the protocol were distributed to and discussed with all the partners in the practices participating in the study. One year later similar analysis showed that record keeping (recording of pulse rate and rhythm) had improved significantly in the group of principals carrying out the audit but not in other principals in these practices. Audit may change only the auditors.